Aide-mémoire on sedation reversal: knowing your way in and out! - Naomi Earl; Burhan Khan (Clinical Medicine, 2025)
Introduction: Conscious sedation is commonly used by respiratory physicians for various procedures. Knowledge and familiarity with sedation and its reversal are essential.We aimed to ascertain the usage of reversal agents and assess the understanding of sedation and antidotes among respiratory trainees. We hypothesised that the knowledge and awareness of sedation reversal is poor and, thus,poses a rare but significant risk to patients. Therefore, we propose formulating an aide-mémoire on sedation reversal to reference in an emergency. Materials and Methods: We quantified the amount of sedation and reversal agents locally dispensed. We anonymously surveyed respiratory trainees in the deanery on knowledge of sedation/antidotes. Results and Discussion: Over the previous 5 years at our Trust, 68,160 mL midazolam and 50,094 mL fentanyl were dispensed compared with only 30 mL naloxone and 350 mL flumazenil.29 trainees completed the survey.Midazolam was the most used sedative (97%) but 7% were unsure of the dosage. 10% did not know the reversal for midazolam. 93% did not know the dose of flumazenil, supplementary dosing or how to prepare it.Alfentanil/fentanyl were second most used, but 29% were unsure of the dosage. 14% did not know the reversal for opioids. 83% did not know the initial or supplementary dosing of naloxone and 100% did not know how to prepare it.96% thought that an aide-mémoire would be useful in clinical practice. Only 10% had access to a local reversal policy at their hospital. Conclusion: Although rare, but often an emergency event, knowledge of sedation reversal is crucial for patient safety, but it is apparent that this is inadequate. A aide-mémoire on sedation reversal (Fig 1) may be invaluable for improving patient safety.